Electrohydraulic lithotripsy through endoscopic retrograde cholangiopancreatography combined with SpyGlass in the treatment of complex pancreatic duct stones: A case report and literature review - Pu, Weigao; Ma, Chenhui; Wang, Bofang; Wang, Yunpeng; Wang, Haiyun; Xu, Bo; He, Puyi; Cui, Hongbin; Chen, Hao (Frontiers in Surgery, 2023)
The incidence of pancreatic duct stones (PDS) is less than 1%. After the formation of stones, the lumen of the pancreatic duct is blocked, and the pancreatic juice cannot be discharged smoothly, resulting in the impairment of the internal and external secretions of the pancreas. Several national guidelines now recommend endoscopic retrograde cholangiopancreatography (ERCP) as the treatment for PDS. The emergence of SpyGlass makes it possible to visualize the ERCP blind area of the pancreatic system directly. Electrohydraulic lithotripsy (EHL) under SpyGlass can crush large and pressure-resistant stones into smaller fragments, significantly improving the success of the endoscopic treatment of large stones. Here, we report a patient presented with acute alcohol-associated pancreatitis, found to have PDS on imaging, who underwent ERCP combined with SpyGlass (EHL), avoiding surgery, reducing trauma, and being discharged from the hospital with a rapid recovery. Therefore, endoscopic therapy is effective and safe for PDS patients. The combination therapy of this patient is the first use of SpyGlass for PDS in our centre, which marks a new stage in the application of endoscopic therapy for pancreatic diseases.